One Hundred Years at the Intersection of Chemistry and Physics The Fritz Haber Institute of the Max Planck Society 1911-2011 - Friedrich, Bretislav (De Gruyter, 2011)
This volume, occasioned by the centenary of the Fritz Haber Institute, formerly the Institute for Physical Chemistry and Electrochemistry, covers the institute's scientific and institutional history from its founding until the present. The institute was among the earliest established by the Kaiser Wilhelm Society, and its inauguration was one of the first steps in the development of Berlin-Dahlem into a center for scientific research. Its establishment was made possible by an endowment from Leopold Koppel, granted on the condition that Fritz Haber, well-known for his discovery of a method to synthesize ammonia from its elements, be made its director. The history of the institute has largely paralleled that of 20th-century Germany. It undertook controversial weapons research during World War I, followed by a "Golden Era" during the 1920s, in spite of financial hardships.